The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1741143220973658
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of research on educational leadership and management in Muslim societies

Abstract: This article reports the results of a systematic review of research on educational leadership and management (EDLM) in Muslim societies. Quantitative methods were employed to examine 362 articles published in eight core international EDLM journals. This review examined general patterns of knowledge production, as well as research topics, conceptual models, and methods employed by scholars in Muslim societies. The results show that 44% of the articles had been published in the past 4 years, and 67% in the past … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 107 publications
0
9
0
1
Order By: Relevance
“…Hallinger and Hammad (2019) stated that they did not find any published review of research in the corpus of Arab-related EDLM publications. In her review of research on EDLM in Muslim societies of which Arabs represent a considerable percentage, Ahmed (2020) reported that reviews of research constituted only 3% of the 362 studies in her sample. Atari and Outum (2019) considered the absence of this line of inquiry as indicator of a weak critical spirit among Arab scholars.…”
Section: Author Biographiesmentioning
confidence: 99%
“…Hallinger and Hammad (2019) stated that they did not find any published review of research in the corpus of Arab-related EDLM publications. In her review of research on EDLM in Muslim societies of which Arabs represent a considerable percentage, Ahmed (2020) reported that reviews of research constituted only 3% of the 362 studies in her sample. Atari and Outum (2019) considered the absence of this line of inquiry as indicator of a weak critical spirit among Arab scholars.…”
Section: Author Biographiesmentioning
confidence: 99%
“…Leadership integrity is meant to guide followers towards achieving a common goal and creating a system where there is happiness and contentment for all. It must be governed by honesty and integrity with an obligation to protect its followers (Ahmed, 2020;Gurmu, 2020;Thien et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The term integrity has many different definitions, including those that refer to the qualities of ethical fairness and honesty. Integrity comes from the Latin word 'integer' which means honesty (Ahmed, 2020;Akbar & Picard, 2020;Ezzani & Brooks, 2019). According to Helgesson and Bülow (2021), Reedy et al (2021) and Palanski & Yammarino (2007), integrity means loyalty that is committed to a strict or honest code of ethics with strong moral principles.…”
Section: Introductionmentioning
confidence: 99%
“…According to Donmoyer (2020, p. 344), none of these issues have been solved and so they continue to create challenges well into the 21st century. The infrequent reviews of the knowledge of the field on national and international scales (Ahmed, 2020;Archbald, 2008;Berkovich & Eyal, 2017;Castillo & Hallinger, 2018;Hallinger & Chen, 2015;Hammad, Samier & Mohammed, 2020;Hallinger & Kovacevic, 2021;Heck & Hallinger, 2005;Gümüş, Bellibaş, Esen & Gümüş, 2018;Gümüş, Bellibas, Gümüş & Hallinger, 2020) were done. Philosophical and epistemological studies (Donmoyer, 2020;Evers & Lakomski, 2012;Fitz, 1999;Haller, 1979;Oplatka, 2008;Oplatka, 2016) have also tried to suggest solutions to the field problems regarding the produced knowledge.…”
Section: Introductionmentioning
confidence: 99%